Best Practices in Counseling Young Female Cancer Survivors on Reproductive Health - Shliakhtsitsava, Ksenya; Suresh, Deepika; Hadnott, Tracy; Su, H. Irene (Seminars in Reproductive Medicine, 2017)
In the United States, there are more than 400,000 girls and young women of reproductive-age with a history of cancer. Cancer treatments including surgery, chemotherapy, targeted therapy, and radiation can adversely impact their reproductive health. This review discusses infertility, contraception, and adverse pregnancy and child health outcomes in reproductive-aged cancer survivors, to increase awareness of these health risks for survivors and their health care providers. Infertility rates are modestly higher, while rates of using contraception and using highly effective contraceptive methods are lower in cancer survivors than in women without a history of cancer. During pregnancy, preterm births are also more common in survivors, resulting in more low-birth-weight offspring. Children of cancer survivors do not have more childhood cancers, birth defects, or chromosomal abnormalities than the general population, with the exception of families with hereditary cancer. Reproductive risks in survivors depend on cancer treatment exposures. For example, women with prior abdominal or pelvic radiation have additional risks of spontaneous abortions, small-for-gestational-age offspring and stillbirths, while those with prior chest radiation or anthracycline exposures have higher risks of cardiomyopathy. To help survivors achieve their reproductive goals safely, family planning and preconception counseling are central to survivorship care.
Keywords: cancer survivor; contraception; fertility; pregnancy; child health